Gemilang Enterprise: friendly pillow / Siti Zur Ain Khairul Aswad [et al.] - Khairul Aswad, Siti Zur Ain; Mat Min, Abdul Lukman; Wahi, Azra Humaira; Mohamad Safri, Nur Syafiqah; Zul Iskandar, Zul Iskandar (2017)
GEMILANG ENTERPRISE is a company which focuses of pillow production in Malaysia. Friendly pillow is one of the Malaysia company that produce a quality and comfortable. The specialty of this pillow, is the customer will find this product is very comfortable and could help them to get enough and quality sleep.